Black's Veterinary Dictionary - Boden, E. (Edward) (London : A. & C. Black, 1998)
This encyclopaedic dictionary offers practical help and reference material to all who handle animals at farms, stables or at home. Entries define and describe information such as viruses, bacteria, and first aid for injured animals.
Previous ed.: 1995.
Keywords: Veterinary medicine -- Dictionaries; Farming and Country Life